Emergence of Edwardsiella piscicida in Farmed Channel ♀, Ictalurus punctatus × Blue ♂, Ictalurus furcatus, Hybrid Catfish Cultured in Mississippi. Issue 2 (11th May 2018) - Griffin, Matt J.; Reichley, Stephen R.; Baumgartner, Wes A.; Aarattuthodiyil, Suja; Ware, Cynthia; Steadman, James M.; Lewis, Marsha; Gaunt, Patricia S.; Khoo, Lester H.; Wise, David J.
Abstract: There is a trend toward the increased incidence and prevalence of Edwardsiella piscicida septicemia in US catfish aquaculture, particularly in channel ♀, Ictalurus punctatus, × blue ♂, I. furcatus, hybrid catfish. From 2013 to 2017, a total of 3242 disease case submissions were made to the Aquatic Research and Diagnostic Laboratory (ARDL) at the Thad Cochran National Warmwater Aquaculture Center in Stoneville, MS. Of these, 1400 (43.2%) were hybrids. E. piscicida was suspected in 138 (4.3%) of cases, the majority of which (89.1%) were from hybrid catfish. A molecular survey of these isolates confirmed the majority (92.0%) to be E . piscicida . Furthermore, cases of E . piscicida from hybrids submitted to the ARDL and the Aquatic Diagnostic Laboratory of the Mississippi State University College of Veterinary Medicine in Starkville, MS, were documented for gross lesions and histological analysis. Grossly, E . piscicida presents with small dermal ulcerations, a raised fluid‐filled cranial midline lesion that is frequently ulcerated, hemorrhage in the gills, exophthalmia, and abdominal distension. Internally, lesions include splenomegaly, straw‐colored ascites, renomegaly, and occasionally hemorrhagic intestines. Histopathological examination is in agreement with gross observations, and infected fish repeatedly demonstrate a mononuclear meningoencephalitis, hemorrhagic branchitis, splenitis, ulcerative dermatitis, granulomatous interstitial nephritis, and hepatitis coupled with a hemorrhagic enteritis.